New fossil species of the Venicoridae (Heteroptera: Pentatomomorpha) from the Lower Cretaceous of Northeast China. (31st December 2016) - Du, Sile; Yao, Yunzhi; Ren, Dong
Abstract: Specimens of the Venicoridae (Heteroptera) occur in the Lower Cretaceous Yixian Formation in northeastern China. We describe a new genus and two new species Halonatusivena shii gen. et sp. nov. and Halonatusivena nervosus sp. nov. from this formation. The veins of the membrane are distinctive; the edges of veins are not simple but resemble an irregular stain, with a reduced vasiform structure previously unknown in the Heteroptera. Remarkably, the antennae of one of the specimens of Halonatusivena shii exhibit morphological abnormality. An identification key for the known species of the Venicoridae is provided.